Climate change, water resources and economic impacts: an analysis of Brazilian hydrographic regions - Rocha, Ademir Antônio Moreira (2022)
In the context of global climate change, one of the biggest challenges is water security. In Brazil, the prospect of water scarcity due to long-run climatic anomalies and the regional disparity between supply and demand for water resources point to limitations and risks to various economic and social activities. Given this scenario, an analysis integrating climate change, water availability, and economic vulnerabilities is necessary to find and apply adequate adaptation and mitigation instruments. Considering the complexity of the issue, we built an Interregional Computable General Equilibrium (ICGE) model named Brazilian Multisectoral and Regional/Interregional Analysis Model with Water Module (BMARIA-H2O) composed of 67 economic sectors and 12 Brazilian hydrographic regions, all this integrated with hydroclimatic modelling. We evaluated two main channels of shock transmission, namely, Channel 1 linked to a change in the price of treated water and Channel 2 related to the capital demand to replace or save raw water. In our modelling, these two channels perform as endogenous ways of adaptation to climate change. We conclude that the economic losses resulting from the effect of climate change on water availability are considerable and are equivalent to a reduction in GDP of BRL 12.3 billion (or US$ 5.2 billion) in the realistic scenario and BRL 29.7 billion (or US$ 12.5 billion) in the pessimistic scenario (year reference 2015). The low substitutability of water (small price elasticity of the water demand) in most user sectors turns price increases into direct shocks to the Brazilian economy. The simulations show that water-intensive sectors, such as water and sewage, forestry production, agriculture, and livestock are the main ones impacted by climate change.